Person-Centered Cultural Assessment Can Improve Child Mental Health Service Engagement and Outcomes. Issue 1 (2nd January 2022) - Sanchez, Amanda L.; Jent, Jason; Aggarwal, Neil Krishan; Chavira, Denise; Coxe, Stefany; Garcia, Dainelys; La Roche, Martin; Comer, Jonathan S.
ABSTRACT: Objective: Disparities in child mental health service engagement suggest traditional evidence-based practices do not properly consider cultural and contextual factors relevant for marginalized families. We propose a person-centered approach to improve the cultural responsiveness of services. Preliminary research supports broadening standard assessments to include a person-centered evaluation of patient cultural factors, however, controlled studies have not been conducted in the context of children's mental health care. Methods: Participants included families (N = 89; 89% racial/ethnic minority) receiving services for child externalizing problems. Prior to intake, caregivers were randomized to receive either Assessment as Usual (AAU) or AAU augmented with the Cultural Formulation Interview (CFI+AAU), a brief caregiver assessment of cultural factors affecting their child's problems and family help-seeking. Results: Implementation data showed strong provider fidelity and clinical utility. Following assessments, CFI+AAU caregivers (relative to AAU caregivers) reported feeling better understood by their provider, and providers reported better understanding CFI+AAU families' values. Caregiver satisfaction was rated highly overall, yet providers reported being more satisfied with the assessment when the CFI was incorporated. Engagement outcomes found CFI+AAU families were significantly more likely than AAU families to subsequently complete the first phase of treatment. Further, among families receiving services in Spanish, CFI+AAU, relative to AAU, was associated with significantly higher treatment attendance, homework completion, and treatment response. Conclusions: The results underscore the utility of incorporating a brief cultural assessment in pretreatment assessments. To improve the cultural responsiveness of services, efforts may do well to promote the uptake of person-centered approaches such as cultural assessment into usual care. Registered at clinicaltrials.gov (NCT03499600).